PENINGKATAN HASIL BELAJAR PASSING ATAS BOLAVOLIMINI MELALUI BANTUAN TUTOR SEBAYA SISWA KELAS V SDN BAWANGAN 2 TAHUN PELAJARAN 2014/2015 - Mohamad Saifudin (STKIP PGRI Jombang, 2013)
ABSTRAKPenelitian ini dilakukan berawal dari permasalahan yang dihadapi guru dalam pembelajaran passing atas bolavoli mini. Oleh karena itu peneliti berupaya untuk mengubah metode dalam mengajarkan teknik passing atas yang selama ini dilakukan oleh guru yaitu metode ceramah dengan metode tutor sebaya. Hal ini dilakukan agar tercipta suasana yang menarik dan menyenangkan dalam belajar teknik passing atas. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (PTK). Sebagai subjek penelitian adalah siswa kelas V SDN BAWANGAN 2 yang berjumlah 23 siswa. Teknik pengumpulan data diperoleh dengan melakukan tes unjuk kerja passing atas bolavoli mini yang dilakukan tiap akhir siklus. Dari hasil penelitian yang telah dilakukan pada siklus satu dengan jumlah klasikal 1635 persentase siswa yang tuntas sebesar 39,13% atau 9 anak dan siswa yang belum tuntas sebesar 60,86% atau 14 anak. Setelah dilaksanakan siklus dua didapat hasil yang maksimal siswa yang tuntas sebesar 78,26% atau 18 anak. Maka penelitian berhenti di siklus dua karena sudah diperoleh hasil yang memuaskan. Dari hasil penelitian yang diperoleh diatas, maka dapat disimpulkan bahwa dengan bantuan tutor sebaya dapat meningkatkan hasil belajar passing atas dalam permainan bolavoli mini siswa kelas V SDN BAWANGAN 2.Kata kunci : Passing atas. Bolavoli mini. Bantuan tutor sebaya. ABSTRACT Saifuddin, Mohamad. 2015. Improved of result learn the over passing on volleyball mini through peer teaching by class V SDN BAWANGAN 2 Academic Year 2014/2015. Advisor: Yudi Dwi Saputra, M.Pd.Keywords: Over passing. VolleyballMini . Peer teaching method.This research was carried out starting from the problems faced by teachers in teaching mini volleyball the over passing. Generally, the most common errors in passing learning on volleyball mini is when learners will do passing on and when receiving volleyball. They tend to fear and panic when receiving the ball from the opponent, so that the passing on less than the maximum. Therefore, researchers are working to change the method in teaching the technique of passing on has been done by the teacher is lecturing with peer tutoring methods. This is done in order to create an atmosphere that is interesting and fun to learn the technique of passing on. In addition, learners can be more active in participating in learning activities, especially sports mini volleyball passing over.The design of this study Classroom Action Research (CAR). The study was conducted in two cycles, one cycle of meetings conducted twice. As research subjects are fifth grade studentsof SDN BAWANGAN 2 classes totaling 23 students. The study was conducted from November 22, 2014 through December 13, 2014. The data collection technique was obtained by testing the performance of passing on a mini volleyball conducted each end of the cycle.From the research that has been done in one cycle, the improvement of learning outcomes obtained passing on volleyball mini through peer tutoring assistance with classical number 1635 with the percentage of students who completed by 39.13% or 9 children and students who have not completed by 60.86% or 14 children. However, continued research on two cycles because there are many students who have not completed the standard goal criteria orKKM (75) in subjects Penjasorkes. Having done two cycles to get maximum results with the percentage of students who completed by 78.26% or 18 children. So stop in cycle two studies because it obtained satisfactory results.According to the result of this research, that the peer tutoring in volleyball mini, it can be increasing the study result of the fifth grade students of SDN BAWANGAN 2.